The baseline fecal microbiome differs in patients with and without anastomotic leakage after colorectal cancer surgery - Anders Bech Jørgensen; Louise Almer; Jose Alfredo Samaniego Castruita; Martin Schou Pedersen; Nikolai Søren Kirkby; Esther Agnete Jensen; Alonzo Alfaro-Núñez; Lennart Friis-Hansen; Birgitte Brandstrup (Heliyon)
Background: Anastomotic leakage (AL) is a severe complication of colorectal surgery. The risk of AL is affected by both surgery and patient factors. Gut microbiomes can be generated from the residual material from the fecal immunochemical test (FIT). We, therefore, examined if AL after colorectal cancer surgery could be associated with specific baseline microbiomes in the FIT screening sampling tubes collected weeks before surgery. Methods: Samples from patients participating in the Danish colorectal cancer screening program were biobanked from 2016 to 2018, and samples from patients who had surgery for screening-detected cancer were included. They were matched with patients without AL in a 1:2 ratio based on age, sex, location of anastomosis (colonic/rectal), ASA classification, and smoking habits. Bacterial DNA was extracted from the sampling tubes, and the fecal microbiomes were analyzed with targeted 16S ribosomal RNA third-generation sequencing. Results: 18 patients who developed AL after surgery were matched with 36 without AL. The alpha diversity was lower in the AL group (p = 0.035), and the AL group separated from the Controls in the PCoA plot (p < 0.001). This was due to the patients undergoing rectal resections, with significant differences in alpha- and beta diversity (p = 0.025 and p = 0.002, respectively). The prevalence of bacteria with the potential to produce collagenase was higher in patients who developed AL (odds ratio 1.29 (95% CI 1.28–1.30), p < 0.001). Conclusions: We found differences in the baseline microbiome profile associated with subsequent development of AL after surgery for screening-detected rectal cancer.